2012
DOI: 10.2165/11599240-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Lacosamide in the Adjunctive Treatment of Patients with Refractory Focal Epilepsy in Belgium

Abstract: In patients with difficult-to-treat epilepsy, standard anti-epileptic drug therapy plus lacosamide appears to be a cost-effective option in Belgium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…Two articles compared lacosamide add-on with standard therapy and calculated an ICUR. Bolin et al 23 found an ICUR of €30,409 per QALY gained, and Simoens et al 24 demonstrated that standard AED therapy plus lacosamide dominated standard AED therapy. Another article compared lamotrigine add-on with standard therapy and calculated an ICER of €1,114 per patient with 50% or more seizure reduction.…”
Section: Aed As Add-on Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Two articles compared lacosamide add-on with standard therapy and calculated an ICUR. Bolin et al 23 found an ICUR of €30,409 per QALY gained, and Simoens et al 24 demonstrated that standard AED therapy plus lacosamide dominated standard AED therapy. Another article compared lamotrigine add-on with standard therapy and calculated an ICER of €1,114 per patient with 50% or more seizure reduction.…”
Section: Aed As Add-on Treatmentmentioning
confidence: 99%
“…25 There was one article comparing pregabalin add-on with standard therapy, calculating an ICUR of €50,193 per QALY and an ICER of €27 per seizure-free day. 26 Maltoni and Messori 27 compared topiramate add-on with standard therapy, calculating an ICUR of €36,831 per QALY gained (24); and Remak et al 28 compared topiramate add-on with clobazam, gabapentin, lamotrigine, and vigabatrin. They calculated an ICUR of €13,246 per QALY gained for topiramate compared with vigabatrin (vigabatrin dominated gabapentin, lamotrigine, and clobazam).…”
Section: Aed As Add-on Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as regards cost-effectiveness only a small number of studies have been published. Thus, the evidence cannot be said to point in any direction yet, even though the studies that have been publish hint that such treatment may be costeffective (6)(7)(8)(9)(10). The existing stock of evidence regarding cost-effectiveness of available adjunctive treatments is (so far) too narrow to support public-policy decisions in most settings, as concluded by a recent review of published cost-effectiveness evidence for newer AEDs (9).…”
Section: Introductionmentioning
confidence: 99%
“…One article included two time horizons (3 months and 2 years). Five studies included children and/or adolescents in addition to adults [38,39,42,48]. Jentink et al focused on teratogenic outcomes of AED treatments and included women intending to have children [41].…”
Section: Resultsmentioning
confidence: 99%